Effect of Mulch Type and Application of Liquid Organic Fertilizer on Pumpkin Plants (Cucurbita moschata) - Robithotul Ummah; Maydella Vista Putri Rinadi (AGARICUS: Advances Agriculture Science & Farming, 2022)
The production of pumpkin (Cucurbita moschata Durch) continues to increase. Optimize the production results, a special treatment is needed. The treatment can be in the form of cultivation techniques such as giving mulch or applying appropriate fertilizers. Research is located on Jl. Kaping Gajah No.45, Jatimulyo Village, Lowokwaru District, Malang City. Observation of parameters: observing the length of the tendrils, number of leaves, number of flowers, fruit weight, diversity of arthropods and intensity of disease in plants. The effect of using black silver plastic mulch (BSPM) is more influential on plant growth and yield than the treatment of black mulch and straw mulch. This is BSPM can suppress weed growth, maintain soil water balance, increase soil surface temperature, increase microorganism activity, keep soil loose, and stimulate root growth. The observations it can be seen that the use of liquid organic fertilizer (LOF) has more effect on plant growth and yield than without using LOF. This is because the use of LOF can stimulate the growth of production branches, and increase the formation of flowers and ovules, and reduce the fall of leaves, flowers and ovules. The use of BSPM and LOF will optimize the growth and yield of pumpkin plants. When use of BSPM and LOF, the soil will remain loose, the activity of soil microorganisms will increase, and the nutrients in the soil will also be maintained.